Pengaruh Jarak Tanam dan Varietas pada Pertumbuhan dan Hasil Tanaman Tomat (Solanum lycopersicum) - Dicky Wahyudi; Pramono Hadi; Libria Widiastuti (JURNAL ILMIAH AGRINECA, 2023)
This study aims to determine the best varieties and planting distances on the growth and yield of tomato plants. This research was conducted in March 2020 until May 2020. This research was carried out in Waru Village, Kuncen Hamlet, BakioSub-District, Sukoharjo District with a height of ± 110 meters above sea level. This study uses an environmental design with the basic pattern of a split plot design with 3 replications. There are two types of treatment factors examined, namely tomato varieties (V) consisting of 3 types: pearl varieties (V1), gem varieties (V2) and serv varieties (V3). The second factor is the treatment of plant spacing (J) consists of 3 types, namely: spacing of 50 x 50 cm (J1), spacing of 60 x 50 cm (J2) and spacingof 70 x50 cm (J3). Data analysis using variance with Fotest at the level of 5% and 1%. If the treatment is significantly different, proceed with the Duncan Multiple Range Test (DMRT) at the 5% level. The results showed that the treatment of varieties (V) showed a significant effect on the parameters of dry stover and significantly affected the parameters of the number of fruit plantations and fruit weight per plot. While no significant effect on plant height and fruit weight parameters per plant. For the treatment of spacing (J) showed a very significant effect on the parameters of the number of fruits peroplant, fruit weightoper plant and weight of fruit per plot. While no significant effect on plant height parameters and dry stover parameters.